POLITISI PEREMPUAN DI TINGKAT LOKAL - Adrianus Chatib (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2020)
Islam by textual and contextual esteem the woman to come up and sit in political podium. On the contrary, not also can be denied by pursuaunt to history fact that political participation of woman predominated by the menfolk politics. What the last, not merely representing just Mid-East Islam picture; however Islam in Indonesia also experience of the same chance; even to purilieus even also there is occult movement symptom to make the political participation of woman of feriferial and subordinat.